HUBUNGAN POLA ASUH DEMOKRATIS ORANGTUA DENGAN KEMANDIRIAN SISWA KELOMPOK B TK NEGERI PEMBINA 3 KOTA PEKANBARU - Afiyah Afiyah; Alucyana Alucyana (Generasi Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2021)
Abstract This study aims to determine the relationship between democratic parenting of parents and the independence of group B students in Binder Kindergarten 3, Marpoyan Damai District, Pekanbaru City. This research was conducted because there were problems in democratic parenting with the independence of group B students. The type of research used is a quantitative approach with a correlational research type. The population of this research is 54 parents. By using a sample census, which means that the entire population will be used as a sample. Data were obtained through a temporary questionnaire for data analysis using normality test analysis, simple linear regression test with the help of SPSS version 14.00 for windows. From the research results, it was found that: the coefficient value of the regression direction between the variables of democratic parenting with the independence of group B students was 0.424 and the significance was t = 0.504. This shows that the variable of democratic parenting at an error rate of 0.05 has a significant effect, and the proposed hypothesis is rejected. The direction of the regression coefficient is positive (+), which means that if the relationship between democratic parenting is better, then the student’s independence will increase by 0.504.